PKM. SD NEGERI 3 APUAN DALAM PENINGKATKAN SDM GURU MELALUI KARYA ILMIAH PTK BERBASIS KEARIFAN LOKAL - I Komang Sukendra; I Dewa Putu Juwana; Ida Ayu Agung Ekasriadi; Putu Dessy Fridayanthi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
SD Negeri 3 Apuan, Susut District, Bangli Regency, in carrying out its activities is under the auspices of the Ministry of Education and Culture. The UPMI PKM team visited SD Negeri 3 Apuan to meet the school principal. From the results of observations and discussions with the principal, and class teachers that at SD Negeri 3 Apuan, there are several problems that need to find solutions such as the teaching and learning process in class, reduced student interest in learning, ICT mastery for teachers, making lesson plans based on local wisdom, making HOTS-based teaching materials, scientific papers or PTK, scientific publications, teacher grades, UKS and so on. Of the several problems that existed at SD Negeri 3 Apuan, the UPMI PKM Team held discussions to decide on priority issues that could be assisted by Partners, namely HR problems, which immediately sought solutions. The implementation method is socialization through training and mentoring. The first activity relates to training on the problem of the teacher's lack of knowledge in writing classroom action research. The activities were carried out in two stages, namely training and mentoring activities. In the mentoring activities for 2 weeks, the mentoring activities aim to improve the target teacher's skills to compose classroom action research writing. This implementation activity involved 2 Mathematics Education Study Program students from PGRI Mahadewa Indonesia University. The results of the Community Partnership Program (PKM) activities resulted in 2 PTK teachers